Cross-cultural decoding of positive and negative non-linguistic emotion vocalizations - Laukka, Petri; Elfenbein, Hillary Anger; Söder, Nela; Nordström, Henrik; Althoff, Jean; Iraki, Frederick Kang'ethe; Rockstuhl, Thomas; Thingujam, Nutankumar S. (Frontiers in Psychology, 2013)
Which emotions are associated with universally recognized nonverbal signals? We address this issue by examining how reliably nonlinguistic vocalizations (affect bursts) can convey emotions across cultures. Actors from India, Kenya, Singapore and USA were instructed to produce vocalizations that would convey 9 positive and 9 negative emotions to listeners. The vocalizations were judged by Swedish listeners using a within-valence forced-choice procedure, where positive and negative emotions were judged in separate experiments. Results showed that listeners could recognize a wide range of positive and negative emotions with accuracy above chance. For positive emotions, we observed the highest recognition rates for relief, followed by lust, interest, serenity and positive surprise, with affection and pride receiving the lowest recognition rates. Anger, disgust, fear, sadness and negative surprise received the highest recognition rates for negative emotions, with the lowest rates observed for guilt and shame. By way of summary, results showed that the voice can reveal both basic emotions and several positive emotions other than happiness across cultures, but self-conscious emotions such as guilt, pride, and shame seem not to be well recognized from nonlinguistic vocalizations.